The glucose uptake of type 2 diabetic rats by Sargassum olygocystum extract: In silico and in vivo studies - Muhamad Firdaus, Rahmi Nurdiani , Bachtiar Rivai, Windy Hapsari Hemassonida, Aqilatul Badzliyah, Nur Khasanah Sugiat (Journal of Applied Pharmaceutical Science, 2022)
This study was to improve the glucose uptake in type 2 diabetic rats by Sargassum olygocystum extract. The identity of S. olygocystum metabolome was determined by high performance liquid chromatography-high resolution mass spectrometry. The value of the energy binding interactions between metabolomes of S. olygocystum and pioglitazone against protein tyrosine phosphatase 1B (PTP1B) was determined by the docking method. Male Rattus norvegicus weighing between 180 and 200 g was used as an experimental animal model for type 2 diabetes mellitus. This experiment consisted of six groups, i.e., normal, diabetes mellitus type 2 (DM2), DM2 + pioglitazone, DM2 + administered with S. olygocystum extract once, twice, and thrice per day, consecutively. The treatment was carried out for 45 days. The parameters were blood glucose, the area under the curve, insulin, homeostasis model assessmentinsulin resistance,, and expression of phosphatidylinositol-3-kinase (PI3K) and Akt. The data were stated as mean and standard deviation, and the differences between the treatments were determined by the Duncan test. The significance level used in this study was 5%. This study showed that S. olygocystum extract capable of reducing the blood glucose and rhamnetin of this seaweed extract enhances the glucose uptake in type 2 diabetic via inhibition of PTP1B activity and inducing PI3K/Akt expression.
Keywords: Brown seaweed extract, glucose uptake, PI3K/Akt, PTP1B, type 2 diabetic rats